Association between glycaemic control and serum lipid profile in type 2 diabetic patients: Glycatedhaemoglobin as a dual biomarker - Alnidawi, Badri Fadhil (AL-Kindy College Medical Journal, 2015)
Background: Patients with type 2 diabetes have an increased prevalence of lipid abnormalities, contributing to their high risk of cardiovascular diseases (CVD).Glycated hemoglobin (HbA1c) is a routinely used marker for long-term glycemic control. In accordance with its function as an indicator for the mean blood glucose level, HbA1c predicts the risk for the development of diabetic complications in diabetic patients[2].Apart from classical risk factors like dyslipidemia, HbA1c has now been regarded as an independent risk factor for (CVD) in subjects with or without diabetes.Objective The aim of this study was to find out association between glycaemic control (HbA1c as a marker) and serum lipid profile in type 2 diabetic patients.Methods This study was conducted in specialized center for Endocrinology and Diabetes (SCED) on 320 type 2 diabetic patient , from May 2009 TO November 2010The variables such as age, sex, family history, physical examination, fasting blood glucose, renal function test, thyroid function test, lipids profile panel test , HbA1c and body mass index (BMI) were analyzed .Dyslipidemia was defined according to the National Cholesterol Education Programme (NCEP) Adult Treatment Panel (ATP) III guidelines. Diabetes was defined according to American diabetes association criteriaWe excluded from this study other causes of dyslipidemia other than DM like uremia,over weight, hypothyroidism and others causes.We selected diabetic patient with ldeal body weight and normal renal function.Results In our study 114 (81%) females out of 132 and 147 (83%) males out of 178 were found tobe dyslipidemic.HbA1c demonstrated positive and significant correlations with total cholesterol(TC), low density lipoprotein cholesterol (LDL-C), high density lipoproteincholesterol (HDL-C) and LDL-C ratio, non-HDL-C and TC/HDL-C ratio.Patients with HbA1c value > 7.0% had significantly higher value of TC,Triglycerid (TG), LDL-C, LDL-C/HDL-C ratio, non-HDL-C and TC/HDL-C ratio ascompared to the patients with HbA1c ≤ 7.0%. However, there was no significantdifference in value of HDL-C between two groups.Conclusion :HbA1c can be used as a potential biomarker for predicting dyslipidemia in type 2diabetic patients in addition to glycemic control.